Non line of sight bidirectional localization in multipath environment - Raharjo Hermawan (2009)
Under conventional Global Positioning System (GPS) localization scheme, several reference devices need to be in Line of Sight (LOS) with the mobile device in order for the algorithm to be able to estimate the location of the mobile device. It uses only LOS information to measure Euclidian distances between reference devices and mobile device and to subsequently construct independent equations needed to estimate mobile device’s position. This conventional method fails if there is insufficient number reference device in LOS with the mobile device. This makes the implementation in indoor environment difficult because indoor environment typically has many obstacles and reflectors. Current state of the art localization scheme is able to locate mobile device in 2-dimensional multipath environment by using both Line of Sight (LOS) and Non Line of Sight (NLOS) bidirectional Time of Arrival (TOA) and Angle of Arrival (AOA) information at both the mobile device and reference device side. This method has significant advantage over conventional localization because the method will be able to work even when no reference device is in LOS with the mobile device and hence this method is suitable for indoor environments.